Treatment of injuries caused by burns: an integrative review (Research, Society and Development, 2022)
The care of the burned patient is complex and requires preparedness from the nursing team, especially the nurse, who is responsible for establishing the needs of the patient, elaborating and supervising the execution of the care plan, and evaluating its effectiveness. Objective: to know and describe the main treatment techniques used in different types of burns, through a review of the available literature. Methodology: this is a qualitative study conducted in the form of an integrative review of the literature. Data collection was performed through searches in the SciELO and Regional Portal of the Virtual Health Library (BVS) databases using the English terms "burn", and "treatment", in addition to the Portuguese terms “queimadura” and “tratamento”, “lesão por queimadura”, “queimadura” and “curativos”, “queimadura” and “hospital”. The singular and plural variations of these terms and search modifiers such as AND or OR were also used to expand the possibility of positive results. The analysis consisted of the synthesis, description, comparison and discussion of the data obtained by reading the articles, through previous tabled organization, using Bardin's analysis (2011). Results: 12 articles were selected in which the main treatment techniques currently used in victims of large burns are observed. Given the various techniques mentioned, the use of silver derivatives continues to be indispensable in the treatment of burns, bringing ample benefits to the patient.